Peningkatan Literasi Digital Dan Minat Belajar Fiqih Melalui Media Berbasis Gamifikasi - AH. SUBHAN (STAI Kuala Kapuas, 2026)
Low student interest in Islamic Jurisprudence (Fiqh) is often caused by monotonous learning methods and minimal use of digital technology. This study aims to analyze the effect of integrating gamification-based learning media using the Quizizz platform on improving digital literacy and student interest in Islamic Jurisprudence. This study used a quantitative approach with a quasi-experimental method through a non-equivalent control group design. The sample consisted of 37 eleventh-grade students divided into an experimental group and a control group. The research instruments included a digital literacy test and a validated student learning interest questionnaire. Data analysis using an Independent Sample T-Test showed a significant difference between the experimental and control groups (p < 0.05). The improvement in the experimental group's performance was demonstrated by an N-Gain value of 0.72, which is in the high category. The results showed that using Quizizz increased student interest through interactive features such as leaderboards, music, and avatars that encourage active engagement and healthy competition. Furthermore, students' digital literacy improved along with their ability to operate the technical features of the Quizizz platform during the learning process. Application of digital gamification in Fiqh learning which simultaneously measures the increase in students' learning interest and digital literacy empirically.